Saliva pH Changes in Patients with High and Low Caries Risk After Consuming Organic (Sucrose) and Non-Organic (Maltitol) Sugar - W, Widowati; SH, Akbar; MH , Tin (IIUM Medical Journal Malaysia, 2013)
Introduction: Enamel demineralization is associated with decrease in saliva pH due to fermentation of sugar by oral commensal. Thus, exploring the changing pattern of saliva pH is meaningful in dental caries prevention. The aim of this study was to compare the changing pattern of saliva pH after consuming different types of sweeteners (sucrose and maltitol). Methods: It was a case-control study involving 14 male patients attending IIUM dental clinic who were selected with the intention of getting seven patients with high caries risk ( DMFT ≥6) and seven patients with low caries risk (DMFT ≤3) with initial saliva pH interval of 6.5 to7.5. Patients were asked to consume snacks containing 8 gram sucrose and 8 gram maltitol as sweeteners. The changing pH values of the saliva were measured by Waterproof pHTestr 10BNC (Oakton, Vernon Hills, USA) seven times consecutively at 0 (before snack consumption), and at 5, 10, 15, 20, 30 and 60 minutes after snack consumption. The pH values of saliva of patients with low and high caries risk after consuming sucrose and maltitol were statistically analized by using Anova and Tukey-HSD tests at α = 0.05. Result: There were significant differences in saliva pH changes between low-risk group and high-risk group after consuming sucrose and maltitol. Conclusion: The changing patterns of saliva pH in high-risk patients were lower than those of low-risk patients after consuming two types of snacks containing sucrose and maltitol.